Frantumaglia: Elena Ferrante's Blurred Lines. - Erens, Pamela (Virginia Quarterly Review)
The article features Italian novelist Elena Ferrante and her works. Topics discussed include her novels that involve a small number of significant characters and take place in highly compressed periods of time, an analysis of "The Ferrante Letters," and information on "The Lying Life of Adults," the first novel she has published since the completion of the Neapolitan quartet.